Response of Water Balance Components to Changes in Soil Use and Vegetation Cover Over Three Decades in the Eastern Amazon - Silva-Júnior, Renato Oliveira da; Souza-Filho, Pedro Walfir Martins e; Salomão, Gabriel Negreiros; Tavares, Alexandra Lima; Santos, Jorge Filipe dos; Santos, Diogo Corrêa; Dias, Luanna Costa; Silva, Marcio Sousa da; Melo, Adayana Maria Queiroz de; Costa, Carlos Eduardo Aguiar de Souza; Rocha, Edson José Paulino da (Frontiers in Water, 2021)
This work aimed to analyze the response of the components of the water balance to changes in land use and cover in the Itacaiúnas River Watershed (Eastern Amazon) over three decades (1980-2013). First, soil texture maps were prepared and combined with the classes of use in each decade, estimate the values of storage and variation in storage of water in the soil. The behavior of the components of the water balance were analyzed according to the Budyko model on the annual scale as a function of the aridity and evaporative indices. In the decade from 2000 to 2009, the remaining forest cover is only 48.91%, while the cover formed by pasture is 50.47%, meaning the water storage capacity in the soil decreased 8.1%. In the 1990s, to 1999, precipitation shows a reduction, probably as a reflection of the very strong events of La Niña and El Niño (1988-1989 and 1997-1998). Observing the sum of the surface area of water bodies in the region and the relationship of forest vs pasture, it is possible to infer that the elevation in evapotranspiration is more related to the increase in evaporation due to the increase in the pasture area than to the reduction transpiration due to forest loss.